International Cooperation and Bioprospecting in Brazil and Peru - DOI: 10.3395/reciis.v1i1.33en - Camila Carneiro Dias; Maria Conceição da Costa (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
This article relates to the "Nature and Impact of North-South, Public-Private Research Partnerships Applied to Bioprospecting" project, which aims to investigate the features of north-south cooperation ain bioprospecting and identify its contribution as a mechanism for the promotion of the scientific and technological capacities of southern countries. The methodology is based on case studies carried out in Brazil, Peru, Colombia and Suriname. The article presents preliminary results of the analysis of bioprospecting practice in two countries, Brazil and Peru, based on the analysis of three bioprospecting arrangements in these countries between 1993 and 2001.